Lack of an association between acute gastroenteritis, acute respiratory infections and malaria in young Gambian children. - Greenwood, B; Byass, P; Greenwood, A; Hayes, R; Menon, A; Shenton, F; Stephens, J; Snow, R (1989)
The incidence of acute gastrointestinal and acute respiratory infections was measured in 2 groups of approximately 750 Gambian children aged 3-59 months during a 3-year period. One group of children was partially protected against malaria by fortnightly chemoprophylaxis with Maloprim whilst children in the other group were infected much more frequently. Mortality from acute gastroenteritis and from acute respiratory infections was similar in the 2 groups. The proportions of children in each group who complained of gastrointestinal or severe respiratory symptoms on morbidity surveillance were also similar. Thus, no evidence was found to suggest that malaria plays either a direct or indirect role in causing acute gastrointestinal or respiratory infections in young children in The Gambia.